Modulated Expression of the Protein Kinase GSK3 in Motor and Dopaminergic Neurons Increases Female Lifespan in Drosophila melanogaster - Trostnikov, Mikhail V.; Veselkina, Ekaterina R.; Krementsova, Anna V.; Boldyrev, Stepan V.; Roshina, Natalia V.; Pasyukova, Elena G. (Frontiers in Genetics, 2020)
Most eukaryotic genes express multiple transcripts and proteins, and a sophisticated gene expression strategy plays a crucial role in ensuring the cell-specificity of genetic information and the correctness of phenotypes. The Drosophila melanogaster gene shaggy encodes several isoforms of the conserved glycogen synthase kinase 3 (GSK3), which is vitally important for multiple biological processes. To characterize the phenotypic effects of differential shaggy expression, we explored how the multidirectional modulation of the expression of the main GSK3 isoform, Shaggy-PB, in different tissues and cells affects lifespan. To this end, we used lines with transgenic constructs that encode mutant variants of the protein. The effect of shaggy misexpression on lifespan depended on the direction of the presumed change in GSK3 activity and the type of tissue/cell. The modulation of GSK3 activity in motor and dopaminergic neurons improved female lifespan but caused seemingly negative changes in the structural (mitochondrial depletion; neuronal loss) and functional (perturbed locomotion) properties of the nervous system, indicating the importance of analyzing the relationship between lifespan and healthspan in invertebrate models. Our findings provide new insights into the molecular and cellular bases of lifespan extension, demonstrating that the fine-tuning of transcript-specific shaggy expression in individual groups of neurons is sufficient to provide a sex-specific increase in survival and slow aging.